2016
DOI: 10.3389/fnhum.2016.00218
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Relaxation of the Foot Reduces Corticospinal Excitability of Hand Muscles and Enhances Intracortical Inhibition

Abstract: The object of this study was to clarify the effects of foot muscle relaxation on activity in the primary motor cortex (M1) of the hand area. Subjects were asked to volitionally relax the right foot from sustained contraction of either the dorsiflexor (tibialis anterior; TA relaxation) or plantarflexor (soleus; SOL relaxation) in response to an auditory stimulus. Single- and paired-pulse transcranial magnetic stimulation (TMS) was delivered to the hand area of the left M1 at different time intervals before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our previous studies using behavioral data showed that force control is more difficult in muscle relaxation than in muscle generation [10]. Some previous studies using fMRI, TMS, and electroencephalography (EEG) reported that neural activation in the M1, supplementary motor area (SMA), PM, dorsolateral prefrontal cortex (DLPFC), and anterior cingulate cortex (ACC) was associated with muscle relaxation [1114]. However, to the best of our knowledge, no previous studies focused on the differences in neural activation of ipsi- or contralateral hemispheres between dominant and non-dominant hands during muscle relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies using behavioral data showed that force control is more difficult in muscle relaxation than in muscle generation [10]. Some previous studies using fMRI, TMS, and electroencephalography (EEG) reported that neural activation in the M1, supplementary motor area (SMA), PM, dorsolateral prefrontal cortex (DLPFC), and anterior cingulate cortex (ACC) was associated with muscle relaxation [1114]. However, to the best of our knowledge, no previous studies focused on the differences in neural activation of ipsi- or contralateral hemispheres between dominant and non-dominant hands during muscle relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…We also used paired-pulse TMS to investigate SICI for the forearm muscles during ipsilateral ankle relaxation. The results revealed that SICI in the M1 forearm region increased during relaxation as compared to that of the resting condition in the ankle (Figure 3; Kato et al, 2016b). This increase in SICI was observed even when the amplitude of the test MEP during relaxation was adjusted to the same amplitude level as that in the resting condition.…”
Section: Coordination Of Multi-limb Muscles Underlying Relaxationmentioning
confidence: 91%
“…As a result, corticospinal excitability of the pronated forearm extensor was temporally suppressed during relaxation of the ankle dorsiflexor. Likewise, excitability of the forearm flexor was suppressed during the planterflexor’s relaxation (Figure 3, Kato and Kanosue, 2016a; Kato et al, 2016b). Therefore, we suggest that muscle relaxation of the foot dorsiflexor produces a state in the hand muscles such that a required contraction is difficult.…”
Section: Coordination Of Multi-limb Muscles Underlying Relaxationmentioning
confidence: 97%
“…Neural crosstalk is considered a possible neuromuscular constraint for movements 41,42) . It is well known that the activity (contraction and relaxation of muscles) of one limb affects not only the corticospinal (or motoneuron) excitability of the muscles employed in the activity, but also the excitability of the resting muscles of other limbs [99][100][101][102][103][104][105][106][107][108][109] . This kind of influence from the activity of one limb to the resting muscles in other limbs is most pronounced between the homologous muscles 110) , but often spread to the non-homologous muscles 111,112) .…”
Section: Experiments 2: Bimanual Finger Tapping In Symmetrical/ Parallmentioning
confidence: 99%